2004
DOI: 10.1063/1.1689643
|View full text |Cite
|
Sign up to set email alerts
|

Folding of small proteins using a single continuous potential

Abstract: Extensive Monte Carlo folding simulations for four proteins of various structural classes are carried out, using a single atomistic potential. In all cases, collapse occurs at a very early stage, and proteins fold into their native-like conformations at appropriate temperatures. The results demonstrate that the folding mechanism is controlled not only by thermodynamic factors but also by kinetic factors: The way a protein folds into its native structure, is also determined by the convergence point of early fol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 31 publications
4
20
1
Order By: Relevance
“…When we define helix formation by native backbone hydrogen bonds, its order is H3, H1, and H2. In the recent computational work of Kim et al, 41 H1 is suggested to be the most stable. The appearance of sustained backbone hydrogen bonds coincides with the beginning of the second folding stage (j > 950).…”
Section: Order Of Helix Formationmentioning
confidence: 99%
“…When we define helix formation by native backbone hydrogen bonds, its order is H3, H1, and H2. In the recent computational work of Kim et al, 41 H1 is suggested to be the most stable. The appearance of sustained backbone hydrogen bonds coincides with the beginning of the second folding stage (j > 950).…”
Section: Order Of Helix Formationmentioning
confidence: 99%
“…20,21 The ab initio folding of FSD has also been attempted by Pak and co-workers 22 and Lee and co-workers. 23 Recently, Hansmann and co-worker 24 and Wang and co-workers 25 applied replica exchange molecular dynamics ͑REMD͒ to the folding study of FSD. The protein in those simulations mostly drifted away from the experimental structure and the most populated conformation was centered at 2.5-4.0 Å, indicating significant artifact in the force fields used in those simulations that made the interpretation of the observed folding events somewhat challenging.…”
Section: 2mentioning
confidence: 99%
“…In the endeavor of obtaining a quantitative agreement between theory and experiments, two small ␣-helical proteins have played a central role, namely the B domain of protein A from Staphylococcus aurues and the Villin headpiece subdomain from chicken. Although these proteins belong to different SCOP fold classes (5), both have simple three-helix bundle native topologies and fold autonomously on the microsecond time scale (6, 7), which makes them ideal test cases for protein simulations and numerous simulation studies, ranging from simple C ␣ Go-type to all-atom models with explicit water, have been undertaken for both protein A (8-21) and Villin (16,17,[22][23][24][25][26][27][28][29].Important advances have been made toward agreements with experiments for both proteins, but several key issues remain unresolved (6, 30, 31). The need for additional studies also is emphasized by recent experiments.…”
mentioning
confidence: 99%